Keberadaan Industri Gula di Jawa dan Dukungan Sistem Usahatani Tebu Sebagai Bahan Baku Industri Sesudah Perubahan KebijakanPergulaan Tahun 1998 =The Existence Of Sugar Industry In Java And The Support Of Sugarcane Supply - Dyah Ismoyowati; Mochammad Maksum; Sri Widodo; Slamet Hartono (Agro Ekonomi, 2003)
Policies change in 1998 influenced Java sugar industry's existence because there was no more obligation to plant sugarcane. This study aims to identify (1) existing sugarcane procurement by the industry, (2) the profitability, in private as well as social prices, of sugarcane farming system as the industry's supplier, and (3) sensitivity analysis on relevant sugar dynamics.The study was conducted on five industry samples spread over Java. The primary data for profitability analysis covered 300 units originated from 185 farmers and 115 industry's plantation units in a proportional spreading.The finding exhibits three alternatives of procurement: (1) partnership with farmers based on minimum return on land, (2) partnership with farmers as the industry provides assistance, and (3) purchasing sugar from free farmers. Using data in 2002, only two samples were financially profitable,-those were east part and west part of Java, while the only region gained social profit was the east part. In spite of that, if social price of sugar using relevant foreign production costs instead of CIE Java has its comparativeadvantage. Sensitivity analysis resulted in Java will achieve financial profit if sugar price rises by 10 percent, or productivity rises by 15 percent, or tariff of 50 percent imposes.